(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
Managerial discourse represents a crucial component of professional communication within modern organizations. It functions not only as a medium for transmitting information but also as a strategic tool for influencing behavior, motivating employees, and regulating institutional processes. The present study investigates the psycholinguistic and pragmatic characteristics of managerial discourse and explores how cognitive mechanisms and contextual language strategies shape managerial communication. The research applies methods of discourse analysis, psycholinguistic interpretation, and pragmatic analysis in order to identify the linguistic patterns typical of managerial speech. Particular attention is given to speech acts, persuasive strategies, and contextual markers that influence interpersonal interaction in organizational settings. The findings demonstrate that managerial discourse is characterized by intentional language use, cognitive framing, motivational rhetoric, and pragmatic strategies such as politeness, implicature, and indirect directives. The study highlights that effective managerial communication depends on the integration of cognitive and pragmatic factors that shape message interpretation and behavioral responses. The results contribute to the understanding of professional discourse and emphasize the importance of interdisciplinary approaches in analyzing managerial communication.